Fertilization impacts on green leafy vegetables supplied with slow release nitrogen fertilizers. (23rd August 2016) - Cai, ShuMei; Zhu, HaiTao; Wang, JuanJuan; Yu, TingYuan; Qian, Xiaoqing; Shan, Yuhua; Tian, Jilin
ABSTRACT: Conventional over-fertilization in green leafy vegetables has promoted the need for alternative nitrogen management practices. A novel slow-release fertilizer, coated with inorganic minerals, was developed in our lab. The membrane structural characteristics and nitrogen release profile of the product were systematically studied. Furthermore, different fertilization treatments were prepared to study the potential nitrogen use efficiency in Brassica chinensis L., cultivated under open field and greenhouse cultivation patterns. With a relatively smooth surface, coating layer of the newly developed fertilizer stacked by bonded multi-layer of polyaryl polymethylene isocyanate was formed by tightly arraying solid phosphate rock powder granules. After immersing the fertilizer in water, there was about 13% nitrogen released after 24 h and 30% of nitrogen released in 7 days. Moreover, the fertilizer significantly enhanced the yield of Brassica chinensis L. by 28.2%. Nitrogen use efficiency of vegetables treated with the fertilizer was much higher than that of conventional fertilization.